General and health-related social media use among adults with children in the household: Findings from a national survey in the United States. Issue 3 (March 2022) - Lama, Yuki; Nan, Xiaoli; Quinn, Sandra Crouse
Highlights: Watching health videos on YouTube was the most popular health-related social media use. Racial/ethnic minorities were more likely to seek out health videos on YouTube. Men were less likely to engage in health-related social media behaviors. Older age, lower education were associated with lower social media use. Abstract: Objective: Examine predictors of social media use among a nationally representative sample of adults with children in the household. Methods: Data were collected from the Health Information National Trends (HINTS) Survey from 2017 to 2020 ( N = 3559). Multivariate logistic regression models assessed the association between sociodemographic variables and social networking site (SNS) use, SNS use to share health information, participation in online forum or support groups for health issues and watching health-related videos on YouTube. Results: Older adults and men were significantly less likely to use social media (p<.05). Non-Hispanic African American (aOR: 1.83; 95%CI: 1.30–2.57), Hispanic (aOR: 2.16; 95%CI: 1.56–2.99), and Asian (aOR: 2.82; 95%CI: 1.67–4.75) adults were more likely to watch health-related videos on YouTube. Conclusions: Racial/ethnic minorities with children in the household were more likely to seek health information on YouTube, highlighting opportunities to disseminate culturally relevant, accurate messages on the platform. Effective health communication targeted to specific demographics can help counter misinformation and promote health behavior particularly during public health emergencies. Practice Implications: Providers need to foster trust so that patients are comfortable to ask questions in addition to seeking information online. Providers can direct patients to credible resources to counter misinformation exposure and promote healthy behavior.